FIGURATIVE EXPRESSIONS MOSTLY USED IN WILLIAM WORDSWORTH’S POEM OF NATURE - Wiadnyana, Dewa Made (Humanis, 2013)
Makalah ini menganalisa tentang kecenderungan penggunaan majas yang muncul dalam tiga puisi William Wordsworth yang masing-masing berjudul “ I Wandered Lonely as a Cloud”, “The World Is Too Much With Us”, “A Whirl - Blast from Behind the Hill”. Teori yang digunakan adalah teori Interpreting Literature oleh K.L Knickerbocker dan Willaiard Reninger
Keywords: Literature, Poetry, Figurative Language